Pengaruh Serat Ijuk Sebagai Bahan Tambah Terhadap Kuat Tarik Belah Beton (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2017)
Concrete is a strong material withstanding compressive strength. The tensile strength of the concrete is only about 9-15% of its compressive strength (Dipohusodo, 1999) and therefore often in the planning of tensile strength of concrete is considered equal to zero.In this research, the researcher tried to apply fiber concrete for the manufacture of concrete that is by addition of fiber of ijuk. Fiber Ijuk is a natural fiber at the base of enau midrib (arenga pinnata), this fiber is very special compared to other natural fibers. The black fibers produced from palm trees have many features that are durable and are not easy to decompose, resistant to acid and salt water, preventing the penetration of soil termites. Fiber fibers have sufficient tensile strength so it is expected to reduce the cracks early and the burden. With the addition of fiber fibers into the mortar is expected to increase the tensile strength of the optimum concrete, and the resulting concrete is lighter.Data of Fiber Research Result obtained by tensile strength of concrete at age 7 days got value for 0% percentage equal to 67,41 kg / cm2, 3% equal to 71,85, 5% equal to 57,04, 8% equal to 70,37, 10% at 48.89. Concrete strength of concrete at age 14 days obtained value for 0% percentage of 68,15, 3% equal to 54,81, 5% equal to 79,26, 8% equal to 60,00, 10% equal to 60,74. Tensile strength of concrete at age 28 day got value for 0% percentage equal to 112,59, 3% equal to 97,04, 5% equal to 107,41, 8% equal to 87,41, 10% equal to 66,67. The decrease in the tensile strength of the fibers mixture due to the more fiber in units of strands it will increase the cracks that occur. Addition of the Ijuk may cause tensile strength to increase if it is in a small percentage.